A study on physical distribution functions practiced by NSTP (M) berhad within Kuala Terengganu / Rusnah Ismail - Ismail, Rusnah (1998)
Since 1996 until April 1996, the sales of Berita Harian and Berita Minggu in Kuala Terengganu have not been encouraging. The sales have been saturated from time to time even government has emphasized on literacy. NSTP (M) Behad as a leading in bahasa newspaper should identify the problems and try to solve it. To accommodate the increasement, the company should examine the effectiveness and efficiency of physical distribution functions such as order processing, inventory control, transportation and warehousing to fulfil the customers order. The company also should identify the factors that affect the effectiveness of intermediaries in selling newspaper. The company may offer various benefits and provide good services to the vendors to encourage them to improve their sales. Regarding to the outlet and early arrival, the company should increase the outlet by appoints more vendors and decrease the number of sub vendors. NSTP (M) Berhad also should improve its technology in printing, order processing and inventory control to ensure the production was efficient and meet the customers need. Lastly, the management should try to solve the problems faced by the vendors such as weather and traffic. With an effective and efficient distribution, the customers will be attracted to buy the newspaper and the company may increase the sales successfully.